Translating and Analyzing Hedging in Tikriti Dialect from Arabic into English - Abdullah, Ghaneya Jasim; Hussein, Shafaa Hady (Integrated Journal for Research in Arts and Humanities, 2023)
Hedging is a linguistic phenomenon used in spoken engagement to communicate interpersonal messages. It is a communicative strategy that allows speakers to soften or regulate the assertiveness of their words. It stems from various characteristics such as uncertainty, doubt, tentativeness. ambiguity, neutrality, mitigation, and subjectivity. Hedging is routinely used in most talks to make statements acceptable to listeners. The current study aims at comparing and analyzing the frequency, types, and purposes of hedges in Tikrit dialect. The study tries to solve the main problem is that there is no research that links the use of hedges with the dialect as a social characteristic. This study is an attempt to fill that gap. The accurate study tries to hypothesize that hedging devices in Tikrit dialect are difficult to be translated into English. And the translators keep the grammatical structure of the hedging devices in the SLTS when translating them into their equivalent TLTs. And hedging devices in Tikrit dialect have the same functions in English. The data selected for the study consists of twenty-three samples taken randomly from 200 typed Tikrit dialect conversations which contain hedging devices. These conversations are of different contexts. Some of them are family conversations, others are street conversations and some others are café conversations. They all share the common feature of being informal. The method of translation (whether covert or overt) used by the translators is going to be figured out. At last, a table for each device is given to summarize the analysis and a proposed translation is offered. Then findings are drawn statistically. The study also draws some key conclusions, the most important of which are that both Arabic and English use hedging devices to show the meaning of hedging devices, and interpreters struggle to render Arabic hedging devices into English. The fundamental cause of these devices' poor representation is their similarity in use. Because they have no experience with this form of translation, the translators do not look for viable counterparts for these devices. As a result, they attempt to avoid utilizing hedging devices whenever possible. and as a result, interpreters are generally weak at applying hedging devices.